A performance académica como ritual de criação e ativismo na era pós-digital - Pérez, P; Pereira, S; Fernandes-Marcos, A (AVANCA CINEMA, 2021)

Book of Proceedings of ARTECH 2021 - 10th International Conference on Digital and Interactive Arts (Hybrid Praxis – Art, Sustainability & Technology) - Lopes, Maria Manuela; Lopes, Paulo Bernardino; Araújo, António; Olivero, Lucas Fabian; Marcos, Adérito Fernandes (2021)

Contemporary art as a factor for knowledge generation from video: A arte contemporânea como fator de geração de conhecimento a partir do vídeo - Urrutia, Hernando; Pérez, Pilar; Fernandes-Marcos, Adérito (10th International Conference on Digital and Interactive Arts, 2021)
0 citations (Crossref) [2022-09-21]

INNOVATING IN OPEN DISTANCE TEACHING WITH FACE-TO-FACE RETREATS WITHIN A DOCTORAL PROGRAM IN DIGITAL MEDIA ART - Fernandes-Marcos, A; Tavares, M (Proceedings of 16th annual International Technology, Education and Development Conference (INTED2022, 2022)
0 citations (Crossref) [2022-09-21] OCLC: 1325332377

Inside the embroidery. The rematerialization of traditional embroidery in a post-digital approach: No interior do bordado. A rematerialização do bordado numa vertente pós-digital - Pereira, Selma; Fernandes-Marcos, Adérito (10th International Conference on Digital and Interactive Arts, 2021)
0 citations (Crossref) [2022-09-21]

Orbital Eccentricity. Sound performance, using commercial and military satellites with real time tracking data - Paquete, Hugo; Bernardino Bastos, Paulo; Fernandes-Marcos, Adérito (10th International Conference on Digital and Interactive Arts, 2021)
0 citations (Crossref) [2022-09-21]
Keywords: Micro Sound; Performance; Sonification; Sound art

Post-Digital Fashion: The Evolution and Creation Cycle - Pereira, Selma; Fernandes-Marcos, Adérito (ZoneModa Journal, 2021)
In the face of the Covid-19 pandemic, the fashion industry was surprised and quickly had to adapt to digital media. However, the relationship between fashion and the multiplicity of screens is not new. Fashion emerged and took its first steps with Cinema, in Modernity. Although there are times when these two systems are further apart from each other, the alliance survived. To analyse contemporaneity, we take as main reference the studies of Gilles Lipovetsky, and his reflections on aesthetic capitalism. The fashion system has many Western fields of life, including art and technology. In this article we discuss how this relationship of fashion adapts and develops with aesthetic capitalism and post-digital art while we analyse representative artefacts from/about fashion. We propose to put the recent digital fashion artefacts in dialogue with post-digital aesthetics theories, discussing the blurred boundaries between the digital and the post-digital, and proposing the instantiation of a post-digital creation cycle applied to fashion artefacts.
Artwork Size: 71-89 Pages Publisher: ZoneModa Journal

Relações entre o pós-digital e o complexo industrial do capitalismo: reformulações sobre a tecnologia como ideologia e lixo digital na arte - Paquete, Hugo; Fernandes-Marcos, Adérito; Bastos, Paulo Bernardino (AVANCA | CINEMA, 2021)
This essay presents a mapping of the historical concepts that contributed to the emergence of post-digital aesthetics and their connections to the concept of post-media in historical terms. It also analyzes the transition from techno-positivism to discourse of resistance against the effects of the capital technological industrial complex and how these advances in technology influence artistic discourses, practices and are the leverage of art and technology which is nothing more than a representation of the aesthetics of capital. Following art and capitalism as an ideology of innovation. Is proposed an unstinting theory about technology, geology, and the importance of these conditions to the post-digital aesthetics in terms of material disponible and conceptual articulation. Producing a reconfiguration of the post-digital conceptual approach as I propose beyond the dysfunctional aesthetics and connected with the concept of radical ecology centered in the usability of electronic garbage and technical obsolescent technologies in the arts.
0 citations (Crossref) [2022-09-21]

Traços transdisciplinares na obra do Padre Manuel Antunes: uma análise crítica à luz da Carta da Transdisciplinaridade /UNESCO-1994 - Mucheroni, M. L; Fernandes-Marcos, A (Repensar Portugal, a Europa e a Globalização – Saber Padre Manuel Antunes, SJ – 100 anos, 2022)
Toda a obra e pensamento do Padre Manuel Antunes se revestem de características de grande abrangência e de capacidade de abertura à inovação, na perspetiva de que o pensamento crítico, sendo perscrutador do desconhecido, enquanto questiona o conhecimento adquirido ou em pesquisa, não se pode fechar em si mesmo ou separar partes do conhecimento de um todo que constitui o universo, e o homem como parte deste, já que se objetiva a compreensão última do Todo. Encontramos, portanto, traços de transdisciplinaridade na obra e pensamento do Padre Manuel Antunes indicando um pioneirismo relativamente ao movimento da transdisciplinaridade que arranca com o primeiro congresso da área e a respetiva carta daí resultante. Neste artigo, os autores propõem uma análise crítica da obra do Padre Manuel Antunes à luz dos princípios fundacionais encontrados na Carta da Transdisciplinaridade de 1994.